A gênese da crítica marxiana ao direito: nas trilhas do vigoroso andarilho - Murilo Leite Pereira Neto (2022)
This thesis investigated the ways Marx’ works approached law during the first years of his intellectual development. For this purpose, priority was given to the production that began still in Marx's student years, going through his doctoral thesis and statements published in the periodical press during the so-called Rhenish Gazette period, finally reaching the material written in Kreuznach and Paris between 1843 and 1844. Our starting point were the discoveries of Brazilian Marxist and philosopher José Chasin, according to whom in 1843, after quitting the Rhenish Gazette, Marx’s thought undergoes a mutation, making it possible to state that until March 1843 there is a pre-Marxian production, and after that, from Kreuznach on,a properly Marxian one. In this thesis, then, we’ve analyzed Marx's thought throughout his intellectual itinerary, from 1837 to 1844, and tried to identify his different positions regarding law. We’ve analyzed thus to what extent the mutation that reached the German author's thought also reaches his position regarding law. From the immanent reading of the texts, the positions regarding law were compared, identifying qualitative change, which resulted in the apprehension of the specific difference between both positions, allowing to spot the genesis of Marx’s critique of law in those texts produced between March 1843 and 1844. Between 1837 and 1844, Marx, although already critical of a certain theory of law made famous in Germany during his time in the university, departs from the defense of law towards a position that sees law solely as an object of criticism, a position that becomes even fiercer when the author moves on to his critique of political economy, establishing a new level of scientificity. On this path, the character of resolving social problems will not be recognized to law, although Marx envisions a certain function of law in the recognition of certain facts resulting from the development of social relations within civil-bourgeois society.